Knowledge and Implementation of the New European Guide in the Management of Arterial Hypertension. The Cigema Survey - Leopoldo Pérez de Isla; Luis Miguel Ruilope; Alejandro de la Sierra; José Zamorano (MDPI AG, 2009)
Knowledge of guideline implementation pitfalls allows anticipation and solving of problems and may help to promote implementation. The aims of this study were: 1) to find out how much is known among medical professionals about the recommendations for the Management of Arterial Hypertension; 2) to study in depth the extent of implementation and 3) to evaluate the manner in which this guide will be applied to daily medical practice. The Delphi method was used for this work. The total estimated sample size was 2,250 physicians. The carefully selected experts answered questionnaires in two or more rounds. The final sample size was 2,475 physicians. Results of the study are detailed in the article. Among the resultsIt is noteworthy that the guide is viewed as needed among all those who have been interviewed and this agreement about its need is generalised and that the improvement in medical practice, together with individual treatment and cardiovascular risk stratification are viewed positively in opinions reached by consensus by the majority of physicians, regardless of whether they are specialists or general practitioners. The main results of this study emphasize the fact that physicians need a guideline for the management of hypertensive patients and that most of physicians agree with them. The new guidelines on arterial hypertension management are widely known among physicians and there appears to be a global agreement regarding the need for the implementation of the new recommendations.